PENGARUH INFUSED WATER KURMA TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL ATERM DI UPTD PUSKESMAS KAWALIMUKTI DINAS KESEHATAN KAB. CIAMIS TAHUN 2022: Effect Of Date Water Infusion On Hemoglobin Levels In Aterm Pregnant Women At Uptd Puskesmas Kawalimukti District Health Department Ciamis Year 2022 - Listiana, Elis Nova; Kasanah , Uswatun; Wahyuni, Sri (LPPM - STIKES Pemkab Jombang, 2023)
Hemoglobin level is a biochemical indicator to determine the nutritional status of pregnant women. Consuming date palm infused water regularly increases iron intake which of course will further increase the hemoglobin level of pregnant women, so that pregnant women who experience complaints and discomfort as a result of the side effects of blood supplement tablets are recommended to consume date infused water This study aims to determine whether there is an effect of date infused water on hemoglobin levels in term pregnant women at the UPTD Kawalimukti Health Office, Ciamis District Health Office in 2022. This type of research was quasi-experimental with a one group pretest posttest design. The population in the study were all term pregnant women at the UPTD Health Center Kawalimukti District Health Office. Ciamis as many as 30 pregnant women. As for the sampling technique using total sampling. The sample in this study were 30 respondents. It can be concluded that the date infused water has an effect on hemoglobin levels in term pregnant women at the UPTD Health Center Kawalimukti District Health Office. Ciamis in 2022 (p value 0.001 > 0.05)